WaterrelationsandgasexchangeinRuilopezia atropurpurea(Asteraceae),agiantrosettegrowingundercontrastingmicroclimatesinthehightropicalAndes (2022)
Tropical high andean ecosystems, known as paramos, are unique because they are highly diverse, have a high number of endemic species, and play an essential role in different ecosystem services, but are especially susceptible to climate change. Most of the giant rosettes, a dominant growth-form in the paramos, depend on unique features like stems protected by marcescent leaves, voluminous stem pith, and leaf pubescence. However, Ruilopezia atropurpurea lacks these characteristics and must respond differently to endure the paramo extreme conditions. Additionally, unlike other rosettes, this species is found under contrasting exposed and understory microenvironments so that intraspecific plasticity is also expected. We evaluated the responses of R. atropurpurea in terms of leaf water relations, gas exchange, and morphological characteristics in temporal (seasonal and daily variations) and spatial (microsite differences) scales in a Venezuelan paramo. R. atropurpurea displayed lower leaf water potentials (minimum leaf water potentials of -1.5 MPa and -1.8 MPa at the turgor loss point), higher leaf conductance (620 mmol m-2s-1), transpiration (5 molm-2s-1), and CO2 assimilation (13 mmol m-2s-1) rates compared to other paramo giant rosettes. A reduction in leaf area and specific leaf area occurred from understory to exposed sites. R. atropurpurea diverges from the typical responses of most paramo giant rosettes to the extreme environmental conditions. This species’ morphological and physiological plasticity permits it inhabit under variable microclimatic conditions, but despite its confirmed plasticity, it is not able to reach higher elevations as other giant rosettes successfully have.